Ownership Rights to Buildings that Stand on Water - Muhammad Tri Mulya Putra; Resiani Corry Djara Liwe; Artha Marina Yonathan Behar; Gianto Umbu Ngailu Deddi (Warmadewa Press, 2024)
Floating houses, or